ABOUT THE STRUCTURE OF CERTAIN THEOREMS OF DIFFERENTIAL CALCULUS - Malešević, Jovan V. (Matematichki Bilten, 2010)
The author presents the structure of certain theorems of differential calculus in the spirit of some eminent mathematicians mentioned in the paper.